2018
DOI: 10.1021/acs.jpcb.8b07552
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Rates of Vibrational Energy Transfer in Proteins with Equilibrium Dynamics and Entropy

Abstract: Theoretical arguments and results of molecular dynamics (MD) simulations of myoglobin at 300 K are presented to relate rates of vibrational energy transfer across nonbonded contacts interacting via short-range potentials to dynamics of the contact. Both theory and the results of the simulations support a scaling relation between the energy transfer rate and the inverse of the variance in the distance between hydrogen-bonded contacts. The results of the MD simulations do not support such a relation for longer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(87 citation statements)
references
References 73 publications
(139 reference statements)
5
80
1
Order By: Relevance
“…We have since examined computationally the relation between the local energy conductivity between non-bonded contacts interacting by hydrogen bonds and the variance in the distance of the hydrogen bond for myoglobin at 300 K (Reid et al 2018). We again found that, for non-bonded contacts interacting by short-range potentials, the energy transfer rate across the contact varies inversely with the variance in the contact length.…”
Section: Energy Exchange Network (Een) For Fixlmentioning
confidence: 92%
See 1 more Smart Citation
“…We have since examined computationally the relation between the local energy conductivity between non-bonded contacts interacting by hydrogen bonds and the variance in the distance of the hydrogen bond for myoglobin at 300 K (Reid et al 2018). We again found that, for non-bonded contacts interacting by short-range potentials, the energy transfer rate across the contact varies inversely with the variance in the contact length.…”
Section: Energy Exchange Network (Een) For Fixlmentioning
confidence: 92%
“…Energy flow in molecules influences chemical reaction kinetics, and the interpretation of a wide range of spectroscopic experiments on proteins requires information about energy relaxation and transport. We recently reviewed the status of computational studies of energy transport in proteins (Leitner and Yamato 2018). Here, we summarize recent developments in that area and new applications.…”
Section: Introductionmentioning
confidence: 99%
“…They also found pathways for energy transport via hydrogen bonds between residues distantly positioned in the sequence of the 35-residue villin headpiece subdomain (Buchenberg et al 2016;Leitner et al 2015). Recently, Leitner and coworkers discussed the rates of vibrational energy transfer for short-range polar contacts, such as hydrogen bonds, as well as at interface in biomolecules in the thermal equilibrium (Leitner et al 2019;Reid et al 2018). They mentioned that analyzing energy transfer across the van der Waals contact using molecular dynamics simulation is challenging because of the small energy conductivity.…”
Section: Mechanism Of Energy Flow In Proteinmentioning
confidence: 99%
“…Since the structure and dynamics of protein molecules are highly anisotropic, the flow of energy and heat should also be anisotropic. By using biophysical computation methods, several groups have been engaged in the characterization of such energy transport processes in proteins [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. We are particularly interested in how the energy relaxation process intervene in proteins control of their biological functions such as allostery.…”
Section: Heat and Energy Flowmentioning
confidence: 99%